A Methodology to Adjust ATMS Observations for Limb Effect and Its Applications. Issue 21 (3rd November 2017) - Zhang, Kexin; Zhou, Lihang; Goldberg, Mitch; Liu, Xingpin; Wolf, Walter; Tan, Changyi; Liu, Quanhua
Abstract: The Advanced Technology Microwave Sounders (ATMS), carried on the Suomi National Polar‐orbiting Partnership (SNPP) satellite, was launched on 28 October 2011. The ATMS is a follow‐on instrument to advanced microwave sounding unit (AMSU), currently flying on National Oceanic and Atmospheric Administration (NOAA) satellites. The primary new ATMS features are a reduced hardware package and improved gap coverage. One thing in common about cross‐track sounders is a scan perpendicular to the motion of the satellite, allowing a broad swath of measurements to be taken. But an undesirable feature is that the measurements vary with scan angle because of changes in the optical pathlength through the Earth's atmosphere between the Earth and the satellite. One approach to this problem is to limb adjust the measurements to a fixed view angle. The limb correction algorithm applied to ATMS is based on the heritage methodology originally applied to MSU and later to AMSU. The limb correction method is applied to each of the 96 ATMS field of view (FOV) per scan line, adjusting the off‐nadir FOV to the nadir view with fitting error generally within the instrumental noise. The limb‐adjusted brightness temperature were used in the original, legacy TIROS Operational Vertical Sounder, and Advanced TIROS Operational Vertical Sounder NOAA sounding product algorithms and more recently to derive the total precipitation water (TPW) retrieval over ocean, with a bias of 0.046 mm and a standard deviation of 3.43 mm, when compared with European Centre for Medium‐Range Weather Forecasts TPW data. The limb‐corrected brightness temperature can be used to detect the atmospheric weather features, such as the warm cores for tropical cyclones, and the imagery presents snapshots for quick weather signal diagnosis. Key Points: The undesirable feature of cross-track sounders is that the measurements vary with scan angle due to limb effect Our limb correction approach is to limb adjust the measurements to a fixed view angle The limb corrected brightness temperature imagery presents snapshots for quick weather signal diagnosis, such as warm cores in tropical cyclones